Activation of the Epstein-Barr virus DNA polymerase promoter by the BRLF1 immediate-early protein is mediated through USF and E2F. - Liu, C (1996)
The Epstein-Barr virus (EBV) DNA polymerase (pol) is essential for the replication of viral genomes during productive EBV infection. We have previously reported that the EBV DNA pol promoter, which is TATA-less and constitutively inactive, is activated by a genomic clone expressing both immediate-early viral transactivators, BZLF1Z and BRLF1 (R), in EBV-infected lymphoid cells. Here we demonstrate that R alone is sufficient to activate the pol promoter in EBV-negative B cells. Unlike other early promoters to which the R protein binds directly, its effect on the pol promoter does not appear to involve a direct DNA-binding mechanism. Instead, we found that two cellular transcription factors, an upstream stimulatory factor USF, and a member of the E2F family of proteins, bind directly to the pol promoter at positions -795 to -786 and -186 to -170, respectively, regions previously identified as important for activation of the pol promoter. These two sites contribute to or are essential for transactivation of the pol promoter by R in EBV-noninfected B cells. These data suggest that the R immediate-early protein may activate a key early EBV promoter (pol) through both USF and E2F.